Parametrization of the Odqvist's Creep Law in the Circular-Symmetrical Problem - Białkiewicz, J.; Piechnik, S. (Engineering Transactions, 1977)
This work presents function parametrization method which describes the state of stress in case of the solution of plane axial symmetrical problems. In result of this parametrization for the simplified law in which the member describing unsteady creep is neglected, the basic equation system can be reduced to a hyperbolic form. In the general formulation of the Odavist's creep law however for the case n=no iteration procedure will be used. The efficiency of calculation method will be illustrated by an example of creep of the disk subjected to the action of pressure inside the hole.